Cooperation and best practices within the COTEC Innovative SME Network - Bento,Paulo (2011)
This article investigates what members consider to be the advantages of cooperating with and belonging to the COTEC Innovative SME Network, and identifies which have been and should be the best cooperation practices. These advantages were measured through enquiries conducted at the beginning of 2008 and 2010, while the best practices were assessed by means of both the 2010 enquiry and the Innovation Scoring (IS). The results were not always conclusive or robust; nevertheless, we found that the three main advantages cited in 2008 were repeated in 2010 and that there are a number of statistically significant relationships between some selected advantages and categories such as ICT sector, manufacturing industry or collaborative profile technological partner. Although the crossing of best practices (past and future) with the IS was inconclusive, the results could serve as a reference for COTEC and its members.